Strategi Pemberdayaan Sumber Daya Manusia Melalui Pendekatan Learning Organization di Kantor BKPSDM Kabupaten Penajam Paser Utara. - Rukaiyah, St; Tangdirerung, Peri; Hamid, Muliyadi (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2024)
This research aims to determine and analyze the Human Resource Empowerment Strategy through the Learning Organization Approach at the BKPSDM Office, North Penajam Paser Regency. The research method used was descriptive qualitative, with six informants as the researcher's primary data source. The research results show that the Strategy for Empowering Human Resources for Apparatus through a Learning Organization Approach at the North Penajam Paser Regency BKPSDM Office from the job training aspect is still not optimal due to budget factors, a discussion forum is needed in formulating policies, non-financial rewards and an adaptive work environment are important in optimizing the learning organization, as well as regular evaluation.